2019
DOI: 10.1002/rmb2.12263
|View full text |Cite
|
Sign up to set email alerts
|

Random‐start ovarian stimulation with aromatase inhibitor for fertility preservation in women with Japanese breast cancer

Abstract: Purpose Fertility preservation is an important issue for young cancer patients. Random‐start controlled ovarian stimulation and double ovarian stimulation have been proposed for efficient oocyte retrieval within the limited time before cancer therapy. We aimed to clarify the efficacy of these new protocols within the Japanese population. Methods We performed a retrospective observational study at a multicenter from February 2012 to August 2017. The study entailed 50 cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Twenty-nine (32%) women initiated the stimulation in the proliferative phase (presence of a dominant follicle) whereas the remaining 61 (68%) started in the luteal phase (presence of a corpus luteum). In the former group, the median (IQR) time between the initiation of the last menses and the initiation of COS was 11 (8)(9)(10)(11)(12)(13)(14)(15) days. In the latter group, it was 22 (18-27) days (p < 0.001).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Twenty-nine (32%) women initiated the stimulation in the proliferative phase (presence of a dominant follicle) whereas the remaining 61 (68%) started in the luteal phase (presence of a corpus luteum). In the former group, the median (IQR) time between the initiation of the last menses and the initiation of COS was 11 (8)(9)(10)(11)(12)(13)(14)(15) days. In the latter group, it was 22 (18-27) days (p < 0.001).…”
Section: Resultsmentioning
confidence: 98%
“…In women recruited after January 2017 when collected oocytes were counted separately for the two ovaries (n = 23), the median (IQR) number of oocytes retrieved in the active and resting ovaries was 7 (4-10) and 9 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), respectively (p = 0.38). The median (IQR) ratio between the number of oocytes retrieved and the number of developed follicles was 0.67 (0.57-1.00) and 0.84 (0.67-1.00), respectively (p = 0.24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, COH can be time consuming as it requires 2-5 weeks for COS [58]. Recent studies have shown stimulating the patient regardless of her menstrual-cycle phase, which is defined as random-start COS, has outcomes similar to conventional early follicular phase-start COS for fertility preservation in cancer patients [59,60]. This protocol would minimize COS cycle to 2-3 weeks, but still time-consuming.…”
Section: Optional Strategies For Fertility Preservation Of Brca Mutatmentioning
confidence: 99%